The prevalence of co-administration of clopidogrel and proton pump inhibitors - Shrestha, Kajal; Hughes, Jeffery; Lee, Ya Ping; Parsons, Richard (Radcliffe Medical Press Ltd., 2011)
Background: Recent studies have suggested that proton pump inhibitors (PPIs) may inhibit the antiplatelet activity of clopidogrel, increasing the risk of major cardiovascular events in patients taking clopidogrel and PPIs together. Aim The primary aim of this study was to determine the prevalence of co-prescription of clopidogrel and PPIs amongst residents of aged-care facilities in New South Wales, Australia. Methods: One-year prescription records of 791 aged-care residents were analysed for prevalence of co-prescribing of clopidogrel and PPIs, and aspirin with clopidogrel and PPIs. Prevalence of co-prescribing of clopidogrel, aspirin and PPI in diabetic patients and clopidogrel with various CYP2C19 inhibitors was also examined. Results: Of the 791 residents studied, 60 were prescribed clopidogrel, 248 were on aspirin and 326 were prescribed a PPI.Among residents who were prescribed PPIs, 155 were prescribed omeprazole, 72 pantoprazole, 15 lansoprazole, 44 esomeprazole and 51 rabeprazole. Eleven of these residents had taken more than one PPI during the study period. Thirty-nine residents took a combination of clopidogrel and a PPI (any PPI) for a mean 203 days (SD 12). Thirteen residents were on the combination of aspirin and clopidogrel for a mean of 202 days (SD 111). Nine residents took the combination of clopidogrel, aspirin and a PPI (any PPI) for a mean of 173 days (SD 81). Only one patient on clopidogrel was receiving a CYP2C19 inhibitor in addition to a PPI. Conclusions: A significant number of residents in this cohort were taking a combination of clopidogrel and a PPI, mainly omeprazole. Residents who were on the combination of clopidogrel and a PPI, with or without aspirin,were on these combinations for a significantly long duration, which could increase their risk of adverse cardiovascular events.